2005
DOI: 10.1186/1743-7075-2-9
|View full text |Cite
|
Sign up to set email alerts
|

Differential effect of obesity on bone mineral density in White, Hispanic and African American women: a cross sectional study

Abstract: Osteoporosis is a major public health problem with low bone mass affecting nearly half the women aged 50 years or older. Evidence from various studies has shown that higher body mass index (BMI) is a protective factor for bone mineral density (BMD). Most of the evidence, however, is from studies with Caucasian women and it is unclear to what extent ethnicity plays a role in modifying the effect of BMI on BMD.A cross sectional study was performed in which records of postmenopausal women who presented for screen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(16 citation statements)
references
References 24 publications
2
14
0
Order By: Relevance
“…Obesity (typically manifested as a higher weight) has been correlated with greater bone mass, bone strength and even bone quality over the life span, mostly as a result of increased mechanical loading 17,18. Mechanical loading stimulates bone formation by decreasing osteoblast apoptosis and also by increasing proliferation and differentiation of osteoblasts and osteocytes 19.…”
Section: Diagnostic Criteriamentioning
confidence: 99%
“…Obesity (typically manifested as a higher weight) has been correlated with greater bone mass, bone strength and even bone quality over the life span, mostly as a result of increased mechanical loading 17,18. Mechanical loading stimulates bone formation by decreasing osteoblast apoptosis and also by increasing proliferation and differentiation of osteoblasts and osteocytes 19.…”
Section: Diagnostic Criteriamentioning
confidence: 99%
“…Several evidences, including those from the NORA study, reported that an increasing BMI is associated with a BMD increase [24]. These observations could be explained taking into account the mechanical load exerted by the increased body weight, which results in an increase of bone mineral density [25].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the body mass index (BMI) was positively associated with aBMD in pre-and postmenopausal women [33,34]. Interestingly, BMI is ethnicity-dependent and can differentially affect various physiological measures [35], including aBMD [36]. This becomes important because very little is known about the relationship of ethnic-specific BMI with aBMD in young populations.…”
Section: Introductionmentioning
confidence: 99%